ANALYSIS PERFORMANCE MEASUREMENT USING BALANCED SCORECARD METHOD AT PERSAHABATAN HOSPITAL, EAST JAKARTA - Firmansyah, Muhamad; Susilowati, Dewi (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
The Balanced Scorecard can translate the organization's vision and mission into operational objectives and measure performance from four perspectives: finance, customers, internal business processes, and learning growth. The purpose of this study was to measure the performance of Persahabatan Hospital using the Balanced Scorecard method. This study used qualitative methods with secondary data published by Persahabatan Hospital in 2020 and 2021 and interviews with informants. The results show that from a financial perspective, the hospital's income growth indicator has increased by 19.67%, and the ROA indicator increased by 0.41%. From a customer perspective, the hospital has seen an increase of 26.5%. From the internal business process perspective, it has been said to be good because it is in line with the vision and mission of Persahabatan Hospital. From a learning growth perspective, employee retention decreased by 25%. These four perspectives of the Balanced Scorecard have a significant impact on hospital performance. The hospital needs to improve service quality by increasing customer acquisition to increase revenue to produce a good performance.